Alias. The complete fourth season [videorecording (DVD)] - Vartan, Michael; Rifkin, Ron; Lumbly, Carl; Garber, Victor (Distributed by Buena Vista Home Entertainment, 2005)
"When Sydney leaves the CIA to join a powerful new Black Ops unit, she has no idea of the reunion in store for her. Family secrets are revealed and old adversaries come together for a year of betrayal, suspense, and breathtaking surprises"--Container.